2018
DOI: 10.1128/jcm.01091-17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Cepheid Xpert TV Assay for Detection of Trichomonas vaginalis with Prospectively Collected Specimens from Men and Women

Abstract: Trichomoniasis is the most prevalent curable sexually transmitted disease (STD). It has been associated with preterm birth and the acquisition and transmission of HIV. Recently, nucleic acid amplification tests (NAAT) have been FDA cleared in the United States for detection of Trichomonas vaginalis in specimens from both women and men. This study reports the results of a multicenter study recently conducted using the Xpert TV (T. vaginalis) assay to test specimens from both men and women. On-demand results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…In a recent study by Schwebke et al (2018); the sensitivity and specificity of Xpert TV were reported to be 96Á4% and 99Á6%, respectively, in vaginal samples. The slightly lower sensitivity could be because they had included 'patient collected' vaginal specimens which may have affected the quality of the sample, in contrast to our study where only vaginal swabs collected by a clinician or trained healthcare professional were used.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In a recent study by Schwebke et al (2018); the sensitivity and specificity of Xpert TV were reported to be 96Á4% and 99Á6%, respectively, in vaginal samples. The slightly lower sensitivity could be because they had included 'patient collected' vaginal specimens which may have affected the quality of the sample, in contrast to our study where only vaginal swabs collected by a clinician or trained healthcare professional were used.…”
Section: Resultsmentioning
confidence: 94%
“…Although the current paradigm is to treat STIs by a syndromic approach, since T. vaginalis infection is frequently asymptomatic, diagnostic testing followed by prompt treatment is essential to avoid serious consequences. Amongst the available formats for the molecular diagnosis of T. vaginalis, the Xpert TV assay (Cepheid, Sunnyvale, CA) has improved the diagnostic capability and is a US-FDA approved NAAT for use in both females and males (Schwebke et al 2018). Amongst laboratory tests, wet mount microscopy has been used traditionally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these technologies will allow for rapid near‐patient testing at the point of care and others have potential for high‐throughput batch testing . Rapid testing using random‐access platforms such as the GeneXpert system (Cepheid, Sunnyvale, CA) may be suitable for in‐clinic testing handling of a low number of specimens, whereas high‐throughput batch testing including the DiaPlexQ assay is useful for laboratories performing a large number of assays …”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity ranges from 95% in patient-collected vaginal swabs to 100% in symptomatic endocervical swabs, with specificities of 99% or higher. 40 A benefit of this assay is that it can be used in settings already using the GeneXpert platform. Indeed, the assay was found to be feasible in antenatal care clinics in Papua New Guinea and among pregnant women living with HIV in South Africa.…”
Section: Trichomoniasismentioning
confidence: 99%